2018
DOI: 10.7196/samj.2017.v108i2.12579
|View full text |Cite
|
Sign up to set email alerts
|

Congenital adrenal hyperplasia due to 21-hydroxylase deficiency in South Africa

Abstract: The diagnosis of CAH is delayed in males and females in both SV and CSW forms of the disorder, which probably contributes to under-reporting of cases and a high mortality rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…Y Gani et al, observed that among 34 children of CAH, 10 children with PPP due to CAH, developed CPP during their follow up in a endocrine clinic of South Africa. 16 Their CPP development was triggered by the chronic mild to moderate intermittent elevation of androgens in patients who are noncompliant with medication like our case. SV boys with advanced bone age of >12 years may have spontaneous CPP when treatment with hydrocortisone is initiated lately.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Y Gani et al, observed that among 34 children of CAH, 10 children with PPP due to CAH, developed CPP during their follow up in a endocrine clinic of South Africa. 16 Their CPP development was triggered by the chronic mild to moderate intermittent elevation of androgens in patients who are noncompliant with medication like our case. SV boys with advanced bone age of >12 years may have spontaneous CPP when treatment with hydrocortisone is initiated lately.…”
Section: Discussionmentioning
confidence: 58%
“…Here, the hydrocortisone suppresses the production of adrenal androgens and stimulates the release of gonadotrophins as inhibitory effects of adrenal androgens disappeared. 16 It appears that proper glucocorticoid replacement to achieve adequate control of hyperandrogenemia during early life might prevent development of CPP in these patients. 14 All the patients were on replacement therapy with hydrocortisone and GnRH analogue after evaluation and in our case, we followed the same footsteps.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The salt-wasting crisis is more common in male newborn, as in the female sex, this condition is detected earlier owing to the virilization of external genitalia. 5,6 The other classic form is the simple virilizing, characterized by virilization of external genitalia, which is more easily detected in female newborns. In this case, a residual activity of 21hydroxylase maintains aldosterone and glucocorticoid production.…”
Section: Casementioning
confidence: 99%
“…Prior to the introduction of newborn screening (NBS) programs for CAH, the neonatal mortality was higher, especially among SW males. This increased mortality was suggested by both the low proportion of the SW form in relation to the SV form and the low male-to-female ratio in the Hospital das Clínicas cohort, as well as in other unscreened populations (9)(10)(11). The CAH NBS program has been applied in Sao Paulo/Brazil since 2013.…”
Section: Introductionmentioning
confidence: 99%